The Sydney Opera House – a modern heritage site’s response to climate change - Matarese, Laura; Bombonato, Emma (Built heritage, 2025)
This paper addresses how the Sydney Opera House (hereafter ‘Opera House’), an UNESCO World Heritage site, has responded to climate change over the past three decades to become a more sustainable heritage site. The implementation of climate actions is critical to conserving and strengthening the Opera House’s cultural heritage significance—the building and its function as a performing arts centre and place for the community. The paper points out that climate action has been, and continues to be, achieved at the Opera House by the organisation’s responsibility for its custodianship by (1) bringing the Opera House team together to tackle climate change through good governance; (2) inspiring positive change in the community through creative programming and engagement; (3) holding the organisation accountable by setting and achieving environmental performance benchmarks; (4) implementing practical mitigation measures that also respect heritage values; and (5) applying a participatory approach to climate risk and adaptation planning. The paper argues that the tangible heritage values of the Opera House (e.g. the building and site) were not adversely affected by the engagement and mitigation actions and that these actions were, in fact, conserved and strengthened the site’s intangible heritage values (e.g. its use). This paper aims to provide an example of sustainable management and climate action by a cultural organisation that serves as the custodian of a heritage site.